Breaking Boundaries: Boosting a Fourth Grader’s Productive English skills with Gamification and Voki in Milagro – Ecuador: Rompiendo barreras: Impulsando el inglés productivo de un estudiante de cuarto grado con gamificación y Voki en Milagro, Ecuador - Castro Tomala, Cristhian Alejandro; Barreno Solorzano, Gabriela Alejandra; José Veliz, Gilberto Antonio; Garaicoa Silva, Gary Andrés (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
This investigation aims to provide a gamified-tool to develop a connectvisit and constructivist teaching and learning, which zeros in on a fourth grader from a public school whose linguistic production will be underscored in detail. The research was qualitative from the outset. Previous to carry out this study case, it was conducted a diagnostic assessment and interview meeting to map out the participants performance’s productive abilities. Throughout the experimentation, a dynamic app along with techniques and strategies based on student-centered were applied, taking into account the fourth-grader' poor knowledge of L2. While the analysis of data sources involves observation, field notes, meetings with the participant’s and participant’s relatives. In the span of putting an ITC tool into practice, linguistic production skyrocketed, enhancing their digital literacy. Therefore, it is posited that e-learning and gamified tools should be designed to assess students’ learning to get extraordinary results.